Biomarcadores de gravidade da COVID-19 - Luporini, Rafael Luís (Universidade Federal de São Carlos, 2022)
Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus, reached pandemic status in 2020, becoming a major global health problem. COVID-19 has a wide spectrum of manifestations, ranging from asymptomatic forms to severe forms such as acute respiratory distress syndrome, cytokine storm and death. Given the magnitude, mortality and morbidity affected in the last two years by COVID-19, this study aimed to identify biomarkers in patients with COVID-19 that establish a relationship with the severity of the disease at hospital admission. Among these biomarkers are inflammatory cytokines, hepatic transaminases and metabolites analyzed by metabolomics. The present research is a unicentric cross-sectional study, conducted at the HU-UFSCar. Clinical, age, sociodemographic, comorbidity and severity data from adult patients hospitalized with COVID-19 were analyzed. Blood samples were collected up to 12 hours after hospital admission. General biochemical analysis, flow cytometry (for inflammatory cytokines IL-2, IL-4, IL-6, IL-10, IFN-γ and TNF-α) and metabolomics by magnetic nuclear resonance were performed for several metabolites, including phenylalanine. After statistical analysis, our results showed that: 1) elderly people with COVID-19 have higher levels of IL-6 and IL-10 compared to the adult group, this difference being associated with the severity of the disease and, in the elderly group, the higher rates of comorbidities. 2) Liver transaminases are markers of COVID-19 severity, with IL-2 associated with borderline transaminase elevations, while IL-10 associated with moderate to severe elevations. 3) Phenylalanine is a severity marker for COVID-19 independent of inflammatory cytokines. In this way, it was possible to establish biomarkers associated with the severity of adult patients with COVID-19 and, thus, to contribute to the analysis of the severity of COVID-19 cases and to assist in the decisions on how to manage cases by health teams in a hospital environment.
Biomarkers of COVID-19 severity
Biomarcadores de gravedad de COVID-19
Keywords: COVID-19; Biomarcadores; Citocinas inflamatórias; Metabolômica; Transaminases; Fenilalanina; Gravidade; Tempestade de citocinas; Phenylalanine; Severity; Cytokine storm; Biomarkers; Metabolomics; Imflammatory cytokines; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::VIROLOGIA; CIENCIAS BIOLOGICAS::BIOQUIMICA::METABOLISMO E BIOENERGETICA; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::ALERGOLOGIA E IMUNOLOGIA CLINICA; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::DOENCAS INFECCIOSAS E PARASITARIAS; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::GASTROENTEROLOGIA; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOLOGIA APLICADA; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOQUIMICA; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA